2022
DOI: 10.1007/s11695-021-05847-3
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Alcohol Use and Disordered Eating Behavior Before and 1 Year After Sleeve Gastrectomy

Abstract: Background Evidence suggests a rise in alcohol misuse after some bariatric procedures. Whether undergoing sleeve gastrectomy raises the risk of high-risk alcohol use is unclear. Objective To characterize the risk of high-risk alcohol use 1 year after sleeve gastrectomy and collect preliminary data on potential associations between disordered eating and high-risk drinking post-surgery. Methods We interviewed 97 patients before and 1 year after sleeve gastrectomy and assessed for high-risk alcohol use via a modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
4
9
0
Order By: Relevance
“…The first superordinate theme indicated that all participants reported they had developed AUD post‐surgery, without preoperative antecedents of problematic alcohol consumption. This is consistent with previous studies suggesting patients with postoperative AUD sometimes develop the disorder de novo after surgery 8,11,16–18,29 . Research indicates that AUD appears about 2 years after surgery and patients first seek treatment 5 years postoperatively 7,8,39 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The first superordinate theme indicated that all participants reported they had developed AUD post‐surgery, without preoperative antecedents of problematic alcohol consumption. This is consistent with previous studies suggesting patients with postoperative AUD sometimes develop the disorder de novo after surgery 8,11,16–18,29 . Research indicates that AUD appears about 2 years after surgery and patients first seek treatment 5 years postoperatively 7,8,39 .…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies suggesting patients with postoperative AUD sometimes develop the disorder de novo after surgery. 8,11,[16][17][18]29 Research indicates that AUD appears about 2 years after surgery and patients first seek treatment 5 years postoperatively. 7,8,39 This coincides with our participants' testimonies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations